Effect of anodizing voltage on surface and physical properties of CNTs incorporated aluminium oxide films - Yaakob, Yazid; Muktar, Muhammad Izzat; A. Aziz, Aflah; Awang Kechik, Mohd Mustafa; Mamat @ Mat Nazir, Md Shuhazlly; Chan, Kar Fei; Mat Tahir, Noor Ayuma; Kamis, Shahira Liza (Malaysian Tribology Society (Mytribos), 2024)
In this study, the surface characteristics of CNTs/Al2O3 films growth from Al alloy were investigated at different anodizing voltage. The samples were anodized in sulphuric acid containing CNTs as electrolyte with the voltage ranging from 5 V to 15 V. Surface morphology and crystal structure were observed with SEM and XRD, while the microhardness was analysed via Vickers hardness tester. The XRD spectra revealed that bare aluminium, AAO and AAO-CNTs composed orthorhombic and γ-Al2O3. The surface topography was examined with 3D Optical Profiler, and the findings showed that higher anodizing voltage leads to higher surface roughness (5.71 μm) and pores dimension (w: 43.69 μm and d: 39.63 μm). By adding CNTs, it can reduce surface roughness to 4.80 μm by 16% with pore dimension (w: 37.79 μm and d: 33.78 μm). It can be supported by SEM-EDX showing that enhancement of CNTs into AAO is believed to reduce the porosity. The Vickers hardness of AAO-CNTs showed the highest value which is 210.40 HV compared to the bare aluminium alloy (130.50 Hv) and AAO (198.60 Hv), as CNTs filled in the porosity of oxide layer. This finding provides an additional knowledge incorporating CNTs into aluminum oxide through anodizing technique.